Firm Productivity and Agglomeration Economies : Evidence from Egyptian Data - Badr, Karim; Rizk, Reham; Zaki, Chahir (Taylor and Francis, 2019)
This paper attempts to shed the light on the nexus between firms’ productivity and economies of agglomeration in Egypt. Using a large dataset of firms in 342 firms’ four-digit activities in 27 regions (62,108 firms), we introduce three measures of agglomeration which are urbanization or firm diversification measured by the number of firms by governorate, localization and specialization measured by the average productivity by governorate and sector (generating externalities and knowledge spillovers) and finally competition measured by the number of firm operating in the same governorate and the same sector. We find strong evidence for the existence of agglomeration in Egypt after controlling for firm age, location, economic activity and legal status. In the Egyptian context, productivity spillovers gained from agglomeration measures outweighed the negative effects of competition implied by congestion. The latter is chiefly due to the lack of good infrastructure. When regressions are run by firm size, location and activity, our main findings show first that micro and small firms are more likely to benefit from localization and diversification compared to medium and large firms. Service firms benefit more from high level of diversification while manufacturing firms gain more benefits from knowledge spillovers and specialization in Egypt.